Evaluation of image quality in chest radiographs - Chand, RB; Thapa, N; Paudel, S; Pokharel, GB; Joshi, BR; Pant, DK (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.2126/joim.v35i1.8899 Journal of Institute of Medicine, April, 2013; 35:50-52